Formation of effective structure of attraction and placement of temporarily free money of clients of bank — legal entities as a way of improvement of policy of a diversification of bank (Путеводитель предпринимателя)
Remember the game of «broken telephone» in which everyone played back in kindergarten. You whisper in each other ’s ear the same word, but at the end of the game it became clear that it had nothing to do with the fact, which was called first.